(untitled) (Sciences & Technology. A, exactes sciences, 2007)
Plasma display panels are becoming one of the major large screens, flat display devices, in spite of their low luminous efficiency, which is about 1 lm/W. Many research works are done to optimize the operation of these panels. A positive column discharge application seems an appreciable solution. A study of a plasma display panel cell functioning in the positive column regime is undertaken. The two-dimensional fluid model on which this work is based shows that the geometry and the physical parameters of the cell play an important role in the limitations of the discharge efficiency. For a sustain electrodes width of 150 μm and a sustain distance (gap) of 566 μm, the efficiency is estimated at more than 46 %.